Investigate the Optimum Agricultural Crops Production Seasons in Salah Al-Din Governorate Utilizing Climate Remote Sensing Data and Agro-Climatic Zoning - Alwan, Imzahim A.; Karim, Hussein H.; Aziz, Nadia A. (Iraqi Journal of Science, 2019)
Agriculture is one of the major sources of livelihood for the Iraqi people as one-third of Iraq population resides in rural areas and depends upon agriculture for their livelihoods. This study aims to estimate the impact of temperature variability on crops productivity across the agro-climatic zones in Salah Al-Din governorate using climate satellite-based data for the period 2000 to 2018. The average annual air temperature based on satellite data was downloaded from the GLDAS Model NOAH025_M v2.1, and interpolates using Kriging interpolation/spherical model. Thirteen strategic crops were selected which is Courgette, garlic, Onion, Sweet Pepper, Watermelon, Melon, Cucumber, Tomato, Potato, Eggplant, Wheat, Barley, and Maize. Temperature requirements for each crop during the growing period were compared with actual temperature from GLDAS data. The study highlighted the impacts of temperature changes on agricultural productivity. The results show that there are some crops that are not achieving optimum productivity, such as Courgette first seasons (December-March), Garlic, Onion, and Cucumber. Whereas, there are other crops that achieve good productivity, such as Courgette second season (March- June), Sweet Pepper, Watermelon, Melon, Tomato, Potato, Eggplant, Maize, Wheat, and Barley. The study recommends proper mitigate and adaptive strategies to enhance the positive and lessen the adverse impacts of temperature changes on crops productivity across agro-climatic zones in Iraq.